THE ROLE OF LAW ENFORCEMENT IN UPHOLDING PRIVACY REGULATIONS TO STRENGTHEN NATIONAL RESILIENCE IN THE DIGITAL ERA - Irfandi (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to explore and analyze the role of law enforcement in upholding privacy regulations as an effort to strengthen national resilience in the digital era, with a particular focus on the implementation of Law Number 27 of 2022 on Personal Data Protection (PDP Law). Employing a descriptive qualitative method based on a literature review, the research examines structural, technical, and institutional challenges in the enforcement of the PDP Law, including low levels of public digital literacy, the absence of comprehensive implementing regulations, and the lack of inter-agency integration. The findings reveal that weak law enforcement increases the risk of cyberattacks on critical infrastructure, diminishes public trust in digital services, and poses the potential for digital economic isolation. The study further highlights the importance of synergy among the government, private sector, civil society, and the media in developing an effective data protection system, supported by capacity-building for law enforcement officers, regulatory harmonization, and the adoption of AI-based legal technologies. Conceptually, successful law enforcement in digital privacy protection not only safeguards individual rights but also serves as a strategic foundation for national resilience.